Allelopathic effects of Jatropha curcas stem extracts on food crops in Tarai area - Rastogi, Akanksha; Singh, Vir (The Indian Journal of Agricultural Sciences, 2020)
Allelopathic effects of Jatropha curcas L. aqueous stem extracts on two varieties each of five food crops, viz. Triticum aestivum (wheat), Zea mays (corn), Oryza sativa (rice), Glycine max (soybean) and Brassica juncea (mustard) were observed in the Tarai area of Uttarakhand in 2017-18. Different concentrations (0%, 5%, 10%, 15% and 20% w/v indicated as T0, T1, T2, T3 and T4, respectively) of Jatrophastem aqueous extract were bio-assayed against germination and seedling growth (plumule and radicle length) of the experimental crops. Significant differences in the normal germination between crops as well as their varieties were observed. Seed germination was significantly reduced (P